Doubling time as a measure of epidemiological spread in COVID-19 - Indumini Gunatilake; Prasad Weerasinghe; Nirma Alpitiarachchi; Indika Gunawardana; Thanuja Ratnayaka; Suwani Dasanayake; Gayani Dissanayake; Ahmed Shiyam; Irshad Mashood; Disala Welgama; Jinadari Amarasena; Iresha Jayawickrama; et al. (College of Community Physicians of Sri Lanka, 2020)
No abstract avalable